Health Economics Review - Graf von der Schulenburg, J.-Matthias
Health Economics Review (HER) is an international high-quality journal covering all fields of Health Economics. A broad range of theoretical contributions, empirical studies and analyses of health policy with a health economic focus will be considered for publication. Its scope includes macro- and microeconomics of health care financing, health insurance and reimbursement as well as health economic evaluation, health services research and health policy analysis. Further research topics are the individual and institutional aspects of health care management and the growing importance of health care in developing countries.